(untitled) (Nordic Journal of African Studies, 1998)
• H. Weiss Relieving but not preventing – Public famine relief in some British colonies in Africa up to 1930 • M. Vehnämäki Adjusted environment: Evidence from Ghana’s structural adjustment program • A. M. Nangend The heartbeat and rhythm of life: The cardinal points in the socio-cultural construction of Bukisu personhood • P. Mikkola Random coincidence in mass comparison: Preliminary analysis of the Nilo-Saharan lexicon • O. Akinwumi The Abakwariga and the economic transformation of the Jukun, Kingdom of Wukari, ca. 1650–1900 • J. A. Ògúnwá The derogation of masculinity in Yorùbá proverbs